Surface energy exchanges and stability conditions associated with convective intense rainfall events on the central Andes of Peru - Flores Rojas, José Luis (2025)
This study presents an in-depth analysis of precipitation patterns, surface energy balance (SEB) components, and atmospheric vertical gradients (AVG) in the Huancayo Geophysical Observatory (HYGO) situated in an agricultural region inside the Mantaro valley within the central Andes of Peru, utilizing data from January 2018 to April 2022 and climatic-scale data from 1965 to 2018. Our findings reveal distinct daily and seasonal precipitation patterns, with peak occurrences in the late afternoon and early evening hours, and a pronounced seasonal variation aligning with dry and rainy periods. Analysis of 21 intense precipitation events linked to convective activity offers crucial insights for weather forecasting and disaster preparedness. These events were identified using in situ gauge pluviometers, the MIRA-35c vertical profiler radar and GPM-IMERG rainfall products. The turbulent energy fluxes: sensible (Qₕ) and latent (Qₑ) were estimated using the aerodynamic flux-gradient method and the ground heat flux to the surface was estimated with the scheme of Foken and Napo. Moreover, the study evaluates the efficacy of the Advanced Regional Prediction System (ARPS) model in analyzing turbulent energy fluxes during these events. A comparison with the bulk aerodynamic method indicated underestimations and overestimations by the ARPS model in predicting Qₕ and Qₑ, respectively, necessitating focused calibration and updates in satellite-derived data. Key observations include significant increases in Qe and horizontal momentum flux () before convective precipitation events, marking them as potential precursor variables. Additionally, notable decreases in water vapor mixing ratio vertical gradient (WMVG) and Richardson number (RIN), along with increases in horizontal wind gradient (HWVG), suggest changes in surface moisture fluxes and boundary layer dynamics, crucial for convective rainfall initiation. This comprehensive analysis underscores the importance of understanding atmospheric dynamics for improved prediction and preparedness strategies in the face of climatic variability.